2012
DOI: 10.1002/anie.201200029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies on the Synthesis, Spectroscopic Data, and Reactions of Formyl Azide

Abstract: Small is beautiful: spectroscopic proof or any other indication for the existence of formyl azide (HC(O)N3) has until now been lacking. Although it liberates dinitrogen much more rapidly than homologous acyl azides, it has been prepared for the first time by four different methods (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 64 publications
5
43
0
Order By: Relevance
“…[13] Indeed, quantum-chemical calculations on the potential energys urface( PES) of the decomposition of HC(O)N 3 supportt he preference of the concerted decomposition pathway,w ith the transition state of the stepwise decomposition to HC(O)N being higher in energy than that of the concerted route. [14] Recently,w eh ave shown that reactive a-oxo-nitrenes can be generated efficiently through the irradiation of a-oxo-azides with an ArF laser in solidn obleg as matrices. [15] For instance, the ArF laser photolysis of the matrix-isolateda cyl azide FC(O)N 3 enabled the direct observation of the carbonyl nitrene FC(O)N, [15a] which was not observed in ap revious study of the photolysis in solid matricesb yu sing am ercuryl amp (l > 200 nm).…”
Section: Introductionmentioning
confidence: 99%
“…[13] Indeed, quantum-chemical calculations on the potential energys urface( PES) of the decomposition of HC(O)N 3 supportt he preference of the concerted decomposition pathway,w ith the transition state of the stepwise decomposition to HC(O)N being higher in energy than that of the concerted route. [14] Recently,w eh ave shown that reactive a-oxo-nitrenes can be generated efficiently through the irradiation of a-oxo-azides with an ArF laser in solidn obleg as matrices. [15] For instance, the ArF laser photolysis of the matrix-isolateda cyl azide FC(O)N 3 enabled the direct observation of the carbonyl nitrene FC(O)N, [15a] which was not observed in ap revious study of the photolysis in solid matricesb yu sing am ercuryl amp (l > 200 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Both syn and anti conformers of CF 3 S(O)N 3 ( Figure S5) undergo stepwise decomposition via the nitrene CF 3 S(O)N.This decomposition pathway is in sharp contrast to carbonyl azides,f or which usually the syn and anti conformers prefer concerted and stepwise decomposition pathways,r espectively. [30] Thea ctivation barrier for the decomposition of syn-CF 3 S(O)N 3 (22.3 kcal mol À1 ;C BS-QB3 level of theory) is comparable to that for the favorable concerted decomposition of syn-HC-(O)N 3 (22.3 kcal mol À1 ;C CSD(F12)(T) level of theory) to HNCO and N 2 , [30] with both compounds quickly liberating N 2 at room temperature.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1] This was initiated by Meldal et al [2] as well as Sharpless et al [3] by the copper(I)-catalyzed cycloaddition of azides onto terminal alkynes, which in contrast to the uncatalyzed reactions, [4] proceed highly regioselectively and occur much more quickly. Further, considerable progress was achieved in the synthesis of organic azides, [10][11][12] which led to the preparation and characterization of highly interesting but heretofore inaccessible compounds such as tetraazidomethane, [13] formyl azide, [14] and azidoacetylene. [1,5] Given that copper ions may have undesired effects in biological systems, the strain-driven addition of azides onto cyclooctyne [6,7] and 5-thiacycloheptyne derivatives [8,9] was designed.…”
Section: Introductionmentioning
confidence: 99%
“…[1,5] Given that copper ions may have undesired effects in biological systems, the strain-driven addition of azides onto cyclooctyne [6,7] and 5-thiacycloheptyne derivatives [8,9] was designed. Further, considerable progress was achieved in the synthesis of organic azides, [10][11][12] which led to the preparation and characterization of highly interesting but heretofore inaccessible compounds such as tetraazidomethane, [13] formyl azide, [14] and azidoacetylene. [15] Herein, we report on the title diazide (9), the carbon skeleton of which is outfitted with a strain energy of at least 63.9 kcal mol -1 .…”
Section: Introductionmentioning
confidence: 99%